Socio-economic inequalities in access to COVID-19 tests in France in 2020: evidence from the EPICOV socio-epidemiological cohort - Pierre-Yves Geoffard; Pierre-Yves Geoffard; Florence Jusot; Antoine Sireyjol; Josiane Warszawski; Nathalie Bajos (Frontiers in Public Health)
BackgroundTesting for COVID-19 has been strongly recommended for individuals experiencing COVID-19-like symptoms or those with a close relative who tested positive. In France, tests were free of charge until mid-October 2021 and became widely available after June 2020. Our main objective was to investigate whether access to COVID-19 testing in France was associated with socio-economic conditions, considering gender and ethno-racial status.MethodsA random population-based cohort survey was conducted in France in May 2020 and November 2020, including 95,388 participants aged 18 and over. We used logistic regressions to identify how having been tested in 2020 was associated with socio-economic status and exposure factors among two groups of individuals. The first group consisted of individuals who had no close relative test positive but reported experiencing COVID-19-like symptoms, such as cough, fever, dyspnea, or sudden onset of ageusia, dysgeusia, or anosmia (N = 12,729). The second group included individuals, with or without symptoms, who reported that a close relative had tested positive for COVID-19 (N = 5,360).FindingsIn both groups, testing was more frequent among individuals living in urban areas. For individuals who had no close relative test positive but reported COVID-19-like symptoms, women were 1.04 (95%CI [1.01–1.06]) more likely than men to be tested, and testing decreased with age up to 35. Individuals holding a university degree were (1.08 [1.04–1.12]) more likely than those who only completed high school to be tested, as well as those in one of the three top income deciles with reference to the bottom decile (OR 1.07, [1.02–1.13] for the top decile). Ethno-racial status was not significantly associated with testing. For respondents who had a close relative test positive, testing was strongly associated with having experienced some symptoms, especially after September 1 (OR 1.34, 95%CI [1.30–1.39]). However, there was no link between testing and income, education, or ethno-racial status.InterpretationWhen an individual experiences symptoms but has no close relative who is positive, the motivation to test to avoid transmitting the virus to relatives by isolating oneself is particularly strong. This strategy makes sense when there are actual possibilities to isolate, which may explain why higher income and education positively impact the propensity to test. For individuals who had a close relative test positive, most socio-economic variables were no longer related to testing once infection risk was controlled for. The availability of tests at no cost is not sufficient in itself to eliminate socio-economic inequalities in testing.